Using Text Messaging Systems as a Class Communication Tool. Issue 4 (2nd October 2018) - Rust, Dianna Z.
Abstract: This article discusses the use of text messaging as an effective way for faculty to communicate with students in between class meetings or within an online course. The benefits of text messaging will be discussed, as well as the tools one faculty member has used when texting students or groups of students. Text messaging can be used to give student "nudges" to increase the likelihood students will act in accordance with what the faculty member expects (i.e., read textbook prior to class, attend tutoring sessions, submit homework on time). It can also be used to streamline group work.